Distribution of multidrug-resistant Enterococcus faecalis and Enterococcus faecium isolated from clinical specimens in the Zainoel Abidin General Hospital, Banda Aceh, Indonesia - ZINATUL HAYATI; ULIL HASRI DESFIANA; SUHARTONO SUHARTONO (Society for Indonesian Biodiversity, 2022)
Abstract. Hayati Z, Desfiana UH, Suhartono S. 2022. Distribution of multidrug-resistant Enterococcus faecalis and Enterococcus faecium isolated from clinical specimens in the Zainoel Abidin General Hospital, Banda Aceh, Indonesia. Biodiversitas 23: 5043-5049. Enterococcus faecalis and Enterococcus faecium are two predominant enterococcal species associated with opportunistic infections, especially in clinical settings. This study aimed to determine the distribution and antibiotic sensitivity of E. faecalis and E. faecium isolated from clinical specimens in the Zainoel Abidin General Hospital during 2019-2022. This study involved isolation, identification, and testing of antibiotic susceptibility of E. faecalis and E. faecium isolates. A total number of 299 enterococcal isolates detected in this study consisting of 233 (7.92%) isolates of E. faecalis and 66 (2.18%) isolates of E. faecium. Both E. faecalis and E. faecium shared phenotypic features in common. Enterococcus faecalis isolates exhibited less sensitivity to benzathine penicillin G, ciprofloxacin, levofloxacin, tetracycline, high-level streptomycin, doxycycline, and fosfomycin. Enterococcus faecium had less sensitive to all tested antibiotics, except for linezolid, vancomycin, and tigecycline. Based on the clinical specimens, enterococci were predominantly found in urine specimens accounting for 42.80%, while based on patient’s age, enterococci were prevalently found in patients aged >46 years accounting for 72%. The distribution of both enterococci was evenly detected in both male and female patients. Based on the wards, enterococci were predominantly detected (50.65%) in patients treated in the internal medicine wards. Overall, the present study suggested the susceptibility of enterococcal pathogens and determined the most effective antimicrobials as empirical therapy to treat the infections. The surveillance programs and infections control should be effectively implemented to manage these multidrug-resistant enterococcal infections particularly within healthcare settings.